2023
DOI: 10.1136/jitc-2023-007114
|View full text |Cite|
|
Sign up to set email alerts
|

Reactivation of low avidity tumor-specific CD8+T cells associates with immunotherapeutic efficacy of anti-PD-1

Abstract: BackgroundCD8+T cells are a highly diverse population of cells with distinct phenotypic functions that can influence immunotherapy outcomes. Further insights on the roles of CD8+specificities and TCR avidity of naturally arising tumor-specific T cells, where both high and low avidity T cells recognizing the same peptide-major histocompatibility complex (pMHC) coexist in the same tumor, are crucial for understanding T cell exhaustion and resistance to PD-1 immunotherapy.MethodsCT26 models were treated with anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Similarly, CAR-T cells expressing high affinity TCRs may be more prone to terminal exhaustion (57), while lower affinity CAR T cells display increased proliferation and in vivo antitumor activity (58,59). Accordingly, PD-1 appears to preferentially inhibit the activation of low-affinity T cells (60), which is in line with several observations indicating that the immunotherapeutic efficacy of anti-PD-1-based ICB is associated with the reactivation of low avidity, tumor-specific lymphocytes (61,62). Although we cannot evaluate the overall avidity of P1A vs P1E-specific lymphocytes in our model (these tumor antigens are presented by distinct MHC molecules whose tumor-cell surface MHC-peptide complex density remains to be established), it is noteworthy that neoantigen specific T cells (P1E-reactive) display a reduced TCR expression in the draining lymph nodes (a privileged site of anti-tumor response generation, (63)), compatible with a sustained, and possibly high avidity interaction of these cells with their cognate Ag/MHC complex.…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, CAR-T cells expressing high affinity TCRs may be more prone to terminal exhaustion (57), while lower affinity CAR T cells display increased proliferation and in vivo antitumor activity (58,59). Accordingly, PD-1 appears to preferentially inhibit the activation of low-affinity T cells (60), which is in line with several observations indicating that the immunotherapeutic efficacy of anti-PD-1-based ICB is associated with the reactivation of low avidity, tumor-specific lymphocytes (61,62). Although we cannot evaluate the overall avidity of P1A vs P1E-specific lymphocytes in our model (these tumor antigens are presented by distinct MHC molecules whose tumor-cell surface MHC-peptide complex density remains to be established), it is noteworthy that neoantigen specific T cells (P1E-reactive) display a reduced TCR expression in the draining lymph nodes (a privileged site of anti-tumor response generation, (63)), compatible with a sustained, and possibly high avidity interaction of these cells with their cognate Ag/MHC complex.…”
Section: Discussionsupporting
confidence: 77%
“…Our recent work on KRAS-G12D specific TCRs suggests that TCRs with affinities in the high nM to low μM range are most effective for anti-tumour function, in line with a 'goldilocks' zone for TCR affinities [2,7,27,28]. However, other models have suggested that low avidity TCRs are superior to higher avidity [29]. More investigations into the affinities of effective anti-tumour TCRs are required to understand the desired biophysical properties of TCRs to be used in the clinic.…”
Section: Discussionmentioning
confidence: 98%
“…In case of a high pMHC affinity and a high pMHC-TCR affinity, the overall avidity shall be high. It is posited that, for the small proportion of the neoepitopes that mediate tumor control in vivo and have a high affinity for MHC I (see Table 1 , and some in Table 2 ), the pMHC-TCR affinity would, of necessity, be low, so that the pMHC-TCR avidity is also low: as recently observed ( 121 124 ), only CD8 + T cells with low to intermediate avidity, but not those with high avidity are able to mediate tumor control.…”
Section: Simplicity On the Other Side Of Complexitymentioning
confidence: 97%